Dryocoetiops krivetsae sp. n. (Coleoptera: Curculionidae: Scolytinae: Dryocoetini), the northernmost species of the genus: conflicts between molecular and morphological data in the tribe Dryocoetini - Kerchev, Ivan A.; Ilinsky, Yury Yu.; Bykov, Roman A.; Mandelshtam, Mikhail Yu. (Zootaxa, 2023)
A new species of bark beetle, Dryocoetiops krivetsae Kerchev, Mandelshtam, Bykov et Ilinsky, sp. n., from the southern part of Primorsky Krai (Russian Far East), is described. This is the northernmost discovery of the Oriental genus Dryocoetiops Schedl, 1957, and the first record of the genus in the Russian fauna. Phylogenetic analysis of nuclear and mitochondrial genes i) confirms an independent lineage of Dryocoetiops krivetsae and ii) indicates numerous conflicts of genera relationships in the tribe Dryocoetini.